Cross-referencing unidentified fish sound data sets to unravel sound sources: a case study from the Temperate Northern Atlantic - Vieira, Manuel; Ríos, Noelia; Muñoz-Duque, Sebastian; Pereira, Jodanne; Carriço, Rita; Fernandez, Marc; Monteiro, João G.; Pais, Miguel Pessanha; Quintella, Bernardo R.; Silva, Gonçalo; Silva, Rodrigo P.; Fonseca, Paulo J.; et al. (Frontiers in Remote Sensing, 2024)
There is growing evidence that studying aquatic acoustic communities can provide ecologically relevant information. Understanding these communities may offer unique insights into species behaviour and ecology, while consolidating passive acoustic monitoring as a tool for mapping the presence of target species or estimating changes in aquatic biodiversity. Fish can be significant soundscape contributors, but most soniferous fish species are yet to be identified. Here, we crossed information of three key fish acoustic communities in the Lusitanian Province of the Temperate Northern Atlantic (the Madeira archipelago, the Azores archipelago and Arrábida in mainland Portugal) to unveil potential sources of unidentified fish sounds. We found that the three communities shared various sound types and we were able to narrow down the list of possible fish sound sources. Several sound types were suggested to be produced by species of the Pomacentridae, Scorpaenidae and Serranidae families. We also observed that the sound type /kwa/, associated with Scorpaena spp., exhibited more variations in the geographic area where more species of this genus are known to be present. This study showcases that, as databases of unidentified fish sounds continue to grow, future comparisons of multiple acoustic communities may provide insights into unknown fish sound sources and sound types.